Analysis of Self-Oscillatory Movement of Bell Bowl Electric Drive - V. I. Lukovnikov; I. A. Roudchenko; N. V. Samovendiouk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2008)
The paper investigates an operation of a self-oscillatory asynchronous electric drive with impact loading in the form of a bell. A mathematical model of the electric drive and a circuit of winding connection of the asynchronous engine for its operation in a self-oscillatory mode have been developed in the paper. Analytical investigation of the mathematical model has been carried out and time diagrams of bell bowl and tongue movement have been constructed.